Marketing Strategy for Cassava Leaf Jerky Business Development in Efforts to Improve the Economy on a Home Industry Scale - Septiandika, Verto; Istiqomah, Riska Nur; Veredila, Diska Cintya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Micro, Small and Medium Enterprises (MSMEs) are business activities carried out by the community. When running a small or medium business, business development is necessary. Business development is carried out for the reason of obtaining maximum profits as long as the planned sales targets are exceeded. The maximum profits obtained will have a big influence on business actors so they can expand and develop their business and also help improve the economy of an entrepreneur. An entrepreneur must also have a sales strategy in developing his business, such as a marketing strategy, updating labels and packaging, to improve any marketing that can help improve the community's economy. This activity is a collaboration between students who are guided by lecturers and Micro, Small and Medium Enterprises (MSME) partners, Cassava Leaf Jerky. The implementation of this service is carried out by producing efficient and more effective marketing so that it can easily increase the amount of cassava leaf jerky production.